Investigation of Toxoplasma gondii in shellfish from Adriatic Sea, Italy - SERACENI, Silva; CULTRERA, Rosario; CONTINI, Carlo; C. Macchia; S. Rubini (ECCMID, 2009)
Objectives: Toxoplasma gondii infections have been reported in a number of marine molluscal bivalve shellfish. How these animals acquire T. gondii from their aquatic environment is not known. Some authors have shown that the Eastern oysters (Crassostrea virginica) from North America can remove T. gondii oocysts from surrounding seawater and retain their infectivity. In order to investigate if T. gondii can be acquired from aquatic environment; we searched T. gondii by a sensitive PCR in a selected shellfish's set (Mytilus galloprovincialis, Tapes philippinarum, Chamaelea gallina, Crassostrea gigas), collected from a restricted tract of Adriatic sea coast (26 km2) at intensive breeding, to evaluate the possibility that these marine bivalves can assume T. gondii oocysts in same way. Methods: T. gondii DNA was investigated by nested PCR on 140 shellfish and seawater specimens. After homogenising, DNA was extracted according to standard protocols and T. gondii B1 gene was amplified. All samples also underwent rigorous bacteriological assays, including the search of biotoxins and harmful algae (Dinophysis spp., Alexandrium ostenfeldii, Protoceratium reticulatum, Lingulodinium polyedrum) according to European legislation (2004; Reg. EU 853/854). Results: No sample did detect T. gondii DNA. However, bacteriological investigation showed Salmonella spp., and E. coli in 8 (5.7%) and 11 (7.8%) specimens, respectively, whereas marine biotoxins (7 of Yessotoxin, 13 of Acid Okadaic) were found in 20 specimen (14.3%). No harmful algae were detected. Conclusions: Although the high rates of either bacteria or marine biotoxins found but not designed for human consumption, the results show that the shellfish are not able to acquire T. gondii or retain infectivity for prolonged periods. Consequently, they should not be a possible source of contamination for humans with possible public health implication